Transformasi Tata Kelola Pemerintahan Desa Berbasis Smart Village Government: Studi Kasus Kabupaten Bandung Barat - Amanita, Aliesa; Andayani, Lily; Ardan, R. Ardini Rakhmania (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
The development of information technology has prompted local governments to adopt more innovative governance models, including the concept of Smart Village Government, as an effort to strengthen the effectiveness of village administration. This research aims to analyze the transformation of digital-based village governance in West Bandung Regency, and to identify the supporting factors, challenges, and its impact on the quality of public services, transparency, and community participation. The research method used is a descriptive-qualitative approach with case studies in several villages that have implemented the smart village program. Data were collected through interviews, observation, and review of official documents. The results show that the implementation of Smart Village Government in West Bandung Regency is capable of improving the efficiency of village administrative services, expanding access to public information, and facilitating community participation through digital platforms. This transformation has also encouraged the increased capacity of village officials in using information technology. However, implementation still faces a number of challenges, such as limited internet infrastructure, uneven digital literacy among the community, and the sustainability of the operational budget for village applications. This research concludes that the success of Smart Village Government is highly determined by the commitment of the local government, multi-stakeholder collaboration, and the strengthening of technology and human resource capacity at the village level. Thus, this model has the potential to be an effective strategy in building modern, transparent, and responsive village governance.